A Review of Rechargeable Zinc–Air Batteries: Recent Progress and Future Perspectives - Ghazanfar Nazir; Adeela Rehman; Jong-Hoon Lee; Choong-Hee Kim; Jagadis Gautam; Kwang Heo; Sajjad Hussain; Muhammad Ikram; Abeer A. AlObaid; Seul-Yi Lee; Soo-Jin Park (Nano-Micro Letters, 2024)
Highlights Recent progress in Zn–air batteries is critically reviewed. Current challenges of rechargeable Zn–air batteries are highlighted. Strategies for the advancement of the anode, electrolyte, and oxygen catalyst are discussed. Future research directions are provided to design commercial Zn–air batteries.